Sexual abuse, shonda and concealment in orthodox Jewish communities - Lesher, Michael (MacFarland & Company, 2014)
"This book is the first to analyze, and attempt to explain the methods by which cases of child sexual abuse have been systematically concealed in Orthodox Jewish communities. The book describes a number of characteristic cases of such cover-ups"--